Total Transformative Learning Model in Child-Friendly School - Marno, Marno; Fitriah, Nurlaeli (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze about; 1) the profile of child-friendly schools in Indonesia, 2) the child-friendly school management model, and 3) the challenges of implementing child-friendly-based management models. A case study qualitative approach with a multi-site design is used in this study. The sites studied selected child-friendly schools representing various levels in Indonesia to obtain comprehensive data. The results showed that the management of child-friendly schools was carried out according to the process, namely planning, organizing, implementing, and supervising the implementation of safe, comfortable, healthy schools, free from acts of violence and discrimination, free to express opinions and participate in making decisions according to their capacity achievement of educational goals. Although the management model developed has different approaches and styles, it refers to a holistic management model that integrates the Total Quality Management Model and the Total Transformative Learning Model. Its main characteristics are sustainable development, growing awareness, and how collegial works. Meanwhile, the challenges faced in implementing Child-Friendly Schools are related to efforts to raise awareness of school residents and parents in forming a mindset according to the Child-Friendly School concept.